Designing Accreditation and Verification Systems : A Guide to Ensuring Credibility for Carbon Pricing Instruments - Partnership for Market Readiness (World Bank, Washington, DC, 2019)
Carbon pricing instruments (CPIs) involve large legal and financial interests. Trust in the accuracy and integrity of the reported data is therefore a prerequisite for a well-functioning instrument. To ensure accuracy and integrity of data, a robust monitoring, reporting, and verification (MRV) system is essential. Verification is critical to enhance trust in a carbon pricing system. Where systems have large financial implications, participation is voluntary, or international exchange of units is planned, this trust is paramount for successful implementation. This guidebook aims to help regulators to better understand their options in designing a verification system tailored to their specific needs and circumstances.